A case-control study on association between shift work and type 2 diabetes mellitus - Can LIU; Jing FAN; Weile WU; Wenjiong LIANG; Yulong LIAN; Suzhen GUAN (环境与职业医学)
BackgroundWith economic development and globalization, shift work has become prevalent across industries. Its relationship with type 2 diabetes mellitus (T2DM) attracts increasing attention.ObjectiveTo thoroughly explore the relationship between shift work and T2DM, and analyze the impacts of specific shift patterns on T2DM, so as to provide a basis for formulating reasonable shift schedules.MethodsWe conducted a 1:2 matched case-control study among adults (20-60 years) who ordered occupational health examinations at the Wuxi No.8 People's Hospital from November to December 2023. The case group comprised 200 T2DM patients, while the controls were 400 age-stratified matched non-diabetic individuals. General demographic characteristics, behavioral habits, medical history, and shift work exposure data (including shift patterns, frequency, and length of service) 5 years prior to diagnosis were collected through standardized questionnaires. Logistic regression adjusted for selected confounders was employed to evaluate the association between shift work and T2DM.ResultsThe logistic regression analysis demonstrated that shift work was associated with an increased risk of T2DM. After adjusting for confounding factors, shift workers had a 3.55 times higher risk of being diagnosed T2DM compared to non-shift workers (OR=3.55, 95%CI: 1.026, 12.263). The risk varied across different shift patterns, and the three-shift two-rotation system showed the highest risk (OR=4.17, 95%CI: 1.921, 9.035), followed by the two-shift system (OR=2.94, 95%CI: 2.016, 4.281) and four-shift three-rotation system (OR=2.66, 95%CI: 1.611, 6.093). Workers with more than 3 monthly shift days had a 2.74-fold increased risk (95%CI: 1.658, 4.512) compared to non-shift workers. Additionally, working more than 8 h daily (OR=1.74, 95%CI: 1.185, 2.562) and having more than 20 years of service (OR=2.51, 95%CI: 1.581, 3.976) were both significantly associated with a higher T2DM risk. The trend tests revealed that each incremental increase in monthly shift days and length of service elevated T2DM risk by 2.61 times (95%CI: 1.813, 3.765) and 1.49 times (95%CI: 1.147, 1.931), respectively (P<0.05).ConclusionShift work is an independent risk factor for T2DM, with three-shift two-rotation system posing the highest risk. Shift frequency, daily working hours, and length of service are all significant factors affecting the risk of T2DM. These findings support industry-specific shift policy reform and targeted glucose monitoring and health interventions are recommended for workers engaged in high-risk shift patterns (e.g., three-shift two-rotation system, frequent shifts) and those with prolonged shift work history (>20 years).